Development of video-analyzer system of analyzing the location of gravity center of human body and comparison of several bodies`parameters of inertia - Li, S.; Guo, R.; Jin, J. (Proceedings of First Joint International Pre-Olympic Conference of Sports Science and Sports Engineering. Volume II: Bio-Mechanics and Sports Engineering., 2008)
The video-analyzer system of analyzing the location of center of gravity was developed based on analyzing the status of application of bodies' parameters of inertia. The system was simple and convenient to perform individual test whether bodies' parameters of inertia applied to excellent athletes or not. It might avoid applying inapplicable bodies' parameters of inertia and reduced the error in video analysis.